Analisis Ketepatan Aplikasi Kiblat dalam Play Store dan Apple App Store: Analysis of Qibla App Accuracy in the Play Store and Apple App Store - Ahmad Zaki , Nurulhuda; Hidayatullah, Damia Batrisya (Jurnal Fiqh, 2025)
In today’s era of modern technology, qibla applications, whether in the Play Store or Apple App Store (iOS), have become the preferred choice of the Muslim community. Qibla applications are favoured because they are easy to use in determining the direction of the Qibla. The community’s reliance on Qibla applications is evident in the millions of downloads every day. This trend shows that qibla applications are the main choice of the Muslim community in the 21st century. However, issues arise not only from magnetic interference, but also from the fact that hundreds of applications available on both Android and iOS systems have not all been tested for accuracy. Therefore, this study was conducted to compare and evaluate the accuracy of 25 selected Qibla applications available on the Play Store and Apple App Store. Data were collected through observational methods, and analysis was carried out using a comparative approach. The findings of the study also show that 68% of qibla applications in both systems have a deviation of less than 3°. This study also demonstrates that Qibla applications on iOS systems are more accurate, with a difference of only 8% compared to those on Android. The study findings also prove that Qibla applications can be used as a reference among Muslim users but must be within the tolerance limits allowed in Malaysia.